Loss of Dkk-1 in osteocytes mitigates alveolar bone loss in mice with periodontitis - Goes, Paula (2019)
Background: Periodontitis is a highly prevalent infection-triggered inflammatory disease that results in bone loss. Inflammation causes bone resorption by osteoclasts, and also by suppression of bone formation via increase of Dickkopf-1 (Dkk-1), an inhibitor of Wnt signaling. Here, we tested the hypothesis that osteocytic Dkk-1 is a key factor in the pathogenesis of periodontitis-induced alveolar bone loss (ABL). Methods: Twelve-week-old femalemice with a constitutive deletion of Dkk-1 specifically in osteocytes (Dkk-1fl/fl;Dmp1:Cre) were subjected to experimental periodontitis (EP). Cre-negative littermates served as controls. EP was induced by placing a ligature around the upper 2nd left molar, the contralateral side was used as control. Mice were killed after 11 days and maxillae removed for micro-CT and histological analyses. The mRNA expression of Dkk-1, Runx2, Osteocalcin, OPG, RANKL, RANKL/OPG ratio, LEF-1, and TCF-7 were assessed in maxillae, while mRNA expressions of TNF and IL-1 were evaluated on gingiva using real-time PCR. Blood samples were collected for Dkk-1, CTX, and P1NP measurement by ELISA. Results: The deletion of Dkk-1 in osteocytes prevented ABL in mice with EP, compared to Cre-negative control mice with EP. Micro-CT analysis showed a significant reduction of bone loss (−28.5%) in EP Dkk-1fl/fl;Dmp1:Cre-positive mice compared to their littermate controls. These mice showed a greater alveolar bone volume, bone mineral density, trabecular number, and trabecular thickness after EP when compared to the Cre-negative controls. The local expression in maxillae as well as the serum levels of Dkk-1 were reduced in Dkk-1fl/fl;Dmp1:Cre-positive mice with EP. The transgenic mice submitted to EP showed increase of P1NP and reduction of CTX-I serumlevels, and increase of TCF-7 expression. Histological analysis displayed less inflammatory infiltrates, a reduction of TNF and IL-1 expressions in the gingiva and fewer osteoclasts in Cre-positive animals with EP. Moreover, in mice with EP, the osteocytic deletion of Dkk-1 enhanced bone formation due to increased expressions of Runx2 and Osteocalcin and decreased expression of RANKL in maxillae. Conclusion: In summary, Dkk-1 derived from osteocytes plays a crucial role in ABL in periodontitis.